Leading Teams #5: Norming - Matthew Gold; Rachel Biderman; Sarah A. Bush; Laura L. Greenhaw; Carrie N. Baker (EDIS)
This publication is part of the Leading Teams series and focuses on the norming stage of team development. This article provides an overview of what leaders and team members should know and includes helpful tips for working through the norming stage of team development. Written by Matthew Gold, Rachel Biderman, Sarah A. Bush, Laura L. Greenhaw, and Carrie N. Baker, and published by the UF/IFAS Department of Agricultural Education and Communication, June 2024.